Supply modulation study for Ericsson MINI LINK - Herrmann, Björn (My University, 2011)
This report presents a feasibility study of envelope tracking for Ericssons radio link system. The analysis is done based on a model of an existing 7 GHz GaAs Power amplifier. From the on the model based analysis the theoretical PAE was found to be 50% compared to the 15% achieved through static biasing. The high capacity radio links which were the basis of this study requires bandwidths up to 100 MHz. Implementing envelope tracking on such a systems introduces problems both for linearization and supply modulation efficiency. By introducing an iterative peak tracking low pass this report shows that the PAE still can be improved by at least 5% with a low efficiency supply modulator. Widening the study and investigating the effect of modulating the supply of the whole amplifier chain showed a potential improvement of 10% The trade off between, reduced PAE improvement in the PA and efficiency improvement in the supply modulator when reducing the bandwidth reduction, was evaluated by simulating a simple envelope amplifier. Using lumped elements the maximum bandwidth achieved was 40 MHz.
Keywords: Informations- och kommunikationsteknik; Hållbar utveckling; Elektronik; Information & Communication Technology; Sustainable Development; Electronics